Handbook of clinical anesthesia - Barash, Paul G. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins/Wolters Kluwer, 2013)
"The Handbook of Clinical Anesthesia, Seventh Edition, is a companion to the parent textbook, Clinical Anesthesia, Seventh Edition. This widely acclaimed reference parallels the textbook and presents content in a concise outline format with additional appendices. The Handbook makes liberal use of tables, graphics, and clinical pearls, to enhance rapid access of the subject matter. This comprehensive, pocket-sized reference guides you through virtually every aspect of perioperative, intraoperative, and postoperative patient care."--Provided by publisher.
section I. Introduction to anesthesiology -- section II. Scientific foundations of anesthesia -- section III. Anatomy and physiology -- section IV. Anesthetic agents, adjuvants, and drug interaction -- section V. Preanesthetic evaluation and preparation -- section VI. Anesthetic management -- section VII. Anesthesia for surgical subspecialties -- section VIII. Perioperative and consultative services.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Anesthesia -- Handbooks, manuals, etc; Electronic books